Digitalization of Sanja Village Vegetation Conservation Through 360° Virtual Exploration to Support Smart Eco-Tourism Development in the Tosari Area - Buana, Randy Tirto; Arum, Tirta Puspa; Widiyanti, Zahra; Handoyo, Budi; Putra, Alfyananda Kurnia (EDUTOURISM Journal Of Tourism Research, 2023)
Tosari Village is one of the tourist support villages in the Bromo Tengger Semeru National Park (TNBTS) area and has a tourist village known as Sanja Village. Sanja Village tourism is a form of ecological conservation, which utilizes the potential of the land with the presence of various vegetation supporting the land which is arranged and this potential is used as an ecotourism area. Based on survey results, observations and interviews with Sanja Desa managers, it is clear that there are still shortcomings in packaging content and tourism branding in the current digital era. So in this case there is a need for technological innovation that is in line with tourism trends, one of which is Virtual Exploration which is able to fully explore tourist destinations virtually. The development of virtual exploration is able to build smart eco-tourism in Sanja village. The development stages in this research start from planning, preparation, implementation and reporting. Through virtual exploration of vegetation conservation, Sanja Desa is able to support the development of smart ecotourism in Tosari village. The development of virtual exploration is a form of digitalization by exploring the diversity of vegetation conservation, ecology and culture in 360°, capable of creating a tourist experience that is realistic to visit before Sanja Village. The digitalization of Sanja village ecotourism is able to create sustainable development of Tosari village.